Student‐teacher relationships and bullying: The role of student social status. (6th December 2017) - Longobardi, C.; Iotti, N.O.; Jungert, T.; Settanni, M.
ABSTRACT: Student–teacher relationships have been shown to influence bullying‐related behaviors in students. This study considered the moderating role of students' social statuses in the classroom. The study sample included 435 students (48.7% females) taken from 18 Italian middle‐school classrooms (i.e., sixth to eighth grade). A multigroup path analysis approach was employed to examine whether the effects of the student‐teacher relationships on bullying‐related behaviors differed among social statuses. The results showed that perceived conflict with the teacher was shown to have a significant positive effect on students' engagement in active bullying for students from all the statuses, except for neglected students. In particular, this effect was more relevant for rejected students. The results showed that social status and student‐teacher relationships integrate and shed light on which roles are taken by young adolescents in school bullying, highlighting that it is important for the teachers to recognize these students.